Analisis Kebijakan Moneter Bank Indonesia Pada Masa Pandemi Covid-19 - Jannah, Ervina Fadhilatul (Journal of Economics and Social Sciences (JESS), 2023)
Introduction/Main Objectives: This study aims to determine how Bank Indonesia set monetary policy during the Covid-19 Pandemic in Indonesia and the monetary policy objectives set by Bank Indonesia during the Covid-19 Pandemic. Research Methods: The method in this research is qualitative by taking a lot of data and reports released by Bank Indonesia and collecting data through library research. Finding/Results: The results of this study indicate several Bank Indonesia policies during the Covid-19 Pandemic, including; accommodative macroprudential policies, rupiah exchange rate stability policies, policies for buying SBN from the secondary market, reducing policy interest rates (BI7DRR), and policies for distributing social assistance with the government. Conclusion: This research concludes that Bank Indonesia was serious about regulating monetary policy during the Covid-19 Pandemic.